Romania : Sixth Review Under the Stand-By Arrangement, and Requests for Waiver of Nonobservance of Performance Criterion, and Request for Modification and Establishment of Performance Criteria-Staff Report; Supplementary Information; Press Release on the Executive Board Discussion; Statement by the Executive Director and the Senior Advisor to the Executive Director for Romania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The comprehensive program supported by the IMF, the European Union, and the World Bank has helped Romania in stabilizing its economy, reversing imbalances, rebuilding confidence of international financial markets, and setting a sustainable economic growth. Executive Directors appreciated the authorities' monetary and financial sector policies, which have been prudent and proactive in preserving financial stability during the crisis. Directors appreciated the strong economic performance of Romania under the program and approved a waiver to maintain the reform momentum and provide additional security against unforeseen shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet